Alternative Fuels Technical and Environmental Conditions - Biernat, Krzysztof (IntechOpen, 2016)
The presented book provides an overview of the most widely used alternative fuels in the power supply systems in spark-ignition engines and compression-ignition engines, such as LPG, CNG and RME, including the assessment of their operational usefulness, especially in terms of environmental impact in urban traffic. The possibilities of optimizing the ignition processes in engines fueled by gas are presented. The monograph also contains the results of exploitation tests with an assessment of the environmental impact of fuels containing oxygen additives in diesel engines. The possibilities of producing a wide range of advanced alternative fuels (biofuels) with the use of microorganisms as raw materials are also presented.